Inovasi Pendidikan Karakter melalui Pembiasaan Sholat Tahajjud dalam Membentuk Sikap Istiqomah Santri Nurul Jannah Kota Probolinggo - Qurrotul Aini; Devy Habibi Muhammad (Edu Journal Innovation in Learning and Education, 2026)
Character education in the modern era faces massive moral disruption challenges. Often, students' discipline in Islamic institutions is reduced to a mere formality dependent on external supervision, making it vulnerable to fading without systemic control. Therefore, an educational innovation capable of converting regulative compliance into inner consciousness is urgently needed. This study aims to comprehensively analyze the innovation of character education through the habituation of tahajjud prayer in shaping the istiqomah attitude of students at the Nurul Jannah Foundation in Probolinggo City. A descriptive qualitative approach with an intrinsic case study design was employed in this research. Data were collected through participatory observation, in-depth interviews, and documentation studies to explore students' subjective spiritual experiences, then analyzed using interactive model techniques. The results indicate that tahajjud prayer habituation is proven to be more than just a routine ritual, but a major catalyst for spiritual transformation that successfully cultivates intrinsic motivation. Through achieving inner peace (sakinah), closeness to Allah (taqarrub), and intense self-reflection space (muhasabah) in the last third of the night, students are able to develop autonomous discipline and mental resilience. Internalization of these values directly impacts the strong character of istiqomah, manifested in consistency of performing obligatory worship, firmness of moral principles, and psychological toughness in facing modern era challenges. The conducive pesantren environment and caretakers' exemplarity amplify this experience into an established habituation. The novelty of this study confirms that true istiqomah character cannot be built solely on external systemic coercion, but must root in authentic spiritual experiences. This recommends reorienting Islamic education models.